Morphological and Grammatical Fragments at the End of Surat Al-Baqarah - Mohammed, Muna Saheb; Jassim, Salam Abdul (Journal of Tikrit University for Humanities, 2025)
This research aims to examine the last two verses of Surat Al-Baqarah (the concluding verses) to extract fragments from them at both the morphological and grammatical levels, and to highlight their beauty, majesty, and splendor. This research presents a linguistic study of the verses of the Holy Quran and its endless miraculous nature.